Extension of Maximal Lifespan and High Bone Marrow Chimerism After Nonmyeloablative Syngeneic Transplantation of Bone Marrow From Young to Old Mice - Kovina, Marina V.; Karnaukhov, Alexey V.; Krasheninnikov, Mikhail E.; Kovin, Artem L.; Gazheev, Sarul T.; Sergievich, Larisa A.; Karnaukhova, Elena V.; Bogdanenko, Elena V.; Balyasin, Maxim V.; Khodarovich, Yury M.; Dyuzheva, Tatyana G.; Lyundup, Alexey V. (Frontiers in Genetics, 2019)
The goal of this work was to determine the effect of nonablative syngeneic transplantation of young bone marrow (BM) to laboratory animals (mice) of advanced age upon maximum duration of their lifespan. To do this, transplantation of 100 million nucleated cells from BM of young syngeneic donors to an old nonablated animal was performed at the time when half of the population had already died. As a result, the maximum lifespan (MLS) increased by 28 ± 5%, and the survival time from the beginning of the experiment increased 2.8 ± 0.3-fold. The chimerism of the BM 6 months after the transplantation was 28%. The data are discussed in the light of the need for mass banking of stem cells (SCs) of young people.